The 1st Repair and Retrofit Reinforced Concrete Beam (3RCB) Workshop 2024 / Afifudin Habulat … [et al.] - Habulat, Afifudin; Ahmad, Hazrina; Mansor, Syahirah; Mohtar, Zul Azmi; Mat Saliah, Soffian Noor (Unit Penerbitan PKAPP, 2024)
The 1st Repair and Retrofit Reinforced Concrete Beam (3RCB) Workshop 2024 was organised by Pengajian Kejuruteraan Awam, Universiti Teknologi MARA (UiTM) Cawangan Pulau Pinang, in January 2024. The seminar aims to provide insight into the repair and retrofit of reinforced concrete (RC) structure, particularly beams. The workshop held in the Heavy Structure Laboratory was attended by 102 students taking the Structural Engineering Laboratory (CES511) course. The workshop covers a range of theoretical topics related to repairing and retrofitting of RC beams. Small groups of students (approximately 3 to 5 students per group) was provided one pre-cracked RC beam for their hands-on experience. Each group was also supplied with Carbon Fibre Reinforced Polymer (CFRP) as the strengthening material and the students must demonstrate their expertise and structural understanding to repair and retrofit the pre-cracked RC beam (Figure 1).